Penggunaan Kapur Palupuh dan Kapur Rao-Rao pada Asphalt Concrete - Wearing Course - Putri, Elsa Eka; Arasy, Reza Maulana; Martua, Parasian Oscar (Jurnal Ilmiah Rekayasa Sipil, 2023)
Indonesia has the many area of the lime production including in the West Sumatra Province. The use of lime as a filler in asphalt mixtures is expected to improve the performance of asphalt mixtures. There are two types of lime used, namely Palupuh and Rao-Rao limestone. This study aims to see the effect of using these 2 types of lime as a filler on Asphalt Concrete-Wearing Course (AC-WC) pavements mixture. The bitumen used is Pen 60/70. Marshall testing was carried out to see the characteristics of the pavement mixture. From Marshall's testing on a pavement without lime, has an optimum asphalt content of 6.015%. Furthermore, with a variation of lime 0%, 25%, 50%, 75%, 100% by weight of filler for both types of lime gave an optimum lime content yield of 50% with an increase in stability of 12.024% and flow of 19.375% for Palupuh lime. Meanwhile, the use of Rao-Rao lime cannot improve the Marshall stability of the AC-WC pavement mixture